Tryptophan Catabolism and Response to Therapy in Locally Advanced Rectal Cancer (LARC) Patients - Crotti, Sara; Fraccaro, Alessandra; Bedin, Chiara; Bertazzo, Antonella; Di Marco, Valerio; Pucciarelli, Salvatore; Agostini, Marco (Frontiers in Oncology, 2020)
In locally advanced rectal cancer patients (LARC), preoperative chemoradiation improves local control and sphincter preservation. The response rate to treatment varies substantially between 20% and 30% and it is an important prognostic factor. Indeed, non-responsive patients are subjected to higher rates of local and distant metastases, and worse survival compared to patients with complete response. In the search of predictive biomarkers for response prediction to therapy in LARC patients, we found increased plasma tryptophan levels in non-responsive patients. On the basis of plasma levels of 5-hydroxy-tryptophan and kynurenine, the activities of tryptophan 5-hydroxylase 1 (TPH1) and indoleamine-2,3-dioxygenases 1 (IDO1)/tryptophan-2,3-dioxygenase (TDO2) have been obtained and data have been correlated to gene expression profiles. We demonstrated that TDO2 overexpression in non-responsive patients correlates with kynurenine plasma levels. Finally, through the gene expression and targeted metabolomic analysis in paired healthy mucosa-rectal cancer tumour samples, we evaluated the impact of tryptophan catabolism at tissue level in responsive and non-responsive patients.